Becoming Matter/Becoming Mother: Wilding in Ali Abbasi’s Border (Gräns) - Tschofen, Monique (Imaginations: Journal of Cross-Cultural Image Studies, 2023)
<span style="caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;">This paper provides an analysis of Ali Abbasi’s film <em style="-webkit-print-color-adjust: exact; caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Border<span style="caret-color: #000000; color: #000000; font-family: Helvetica, arial, sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;"> through a feminist new materialist approach that centers what I call “wilding”—a process of worlding that challenges binary and rigid structures of thought that dichotomize existence into fixed categories through the cultivation of bewilderment, a state of openness to not-knowing which requires the unlearning of anthropocentric epistemologies. Paying attention to the etymological roots of the word “matter” (as body, wood, mother/nourishment, and place), the paper shows how the film displaces the dominion of sight with an emphasis on symbiosis that foregrounds the sense of touch